2017
DOI: 10.3391/bir.2017.6.2.14
|View full text |Cite
|
Sign up to set email alerts
|

First morphological and molecular confirmed report of the invasive tropical fire ant, Solenopsis geminata (Fabricius, 1804) (Hymenoptera: Formicidae) from Côte d’Ivoire (West Africa)

Abstract: Lionfishes are conspicuous and disruptive predators once introduced outside of their native range. Here we provide a revision of the occurrences of the common lionfish Pterois miles (Bennett, 1828) in the Mediterranean Sea, showing its rapid geographical expansion since 2012. A single lionfish was photographed in September 2016 during a scientific survey off the Vendicari coast, Southern Sicily, Italy. This is the first record of this notorious invasive species from Italian waters. Given its large size, consp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Exotic forest was also dominated by the highly invasive Pheidole megacephala. Another study indicated that this species is adapted to different land uses mainly cleared, open (Vanderwoude et al 2000) and disturbed environments (Kouakou et al 2017). Another study showed that Pheidole megacephala is a highly invasive species (Horwood 1988), able to gradually replace native ants (AntWeb 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exotic forest was also dominated by the highly invasive Pheidole megacephala. Another study indicated that this species is adapted to different land uses mainly cleared, open (Vanderwoude et al 2000) and disturbed environments (Kouakou et al 2017). Another study showed that Pheidole megacephala is a highly invasive species (Horwood 1988), able to gradually replace native ants (AntWeb 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was commonly found in open woodlands, human settlements, tropical dry forest and along the roads (AntWeb 2020). Its specific microhabitat preferences include dead trees, spaces under rocks and tree barks, living and dead tree branches (Kouakou et al 2017). The occurrence of Pheidole punctulata and Pheidole megacephala and their restriction to the secondary forest made of exotic tree species might be related to their adaptations to the conditions and structure of the secondary forest.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis revealed that 15 morphospecies out of 19 confirmed with DNA based identified species (Ng’endo et al 2013). However, first molecular analysis of S. geminate confirmed invasion and distribution of this invasive species in Cote d’Ivoire, West Africa (Kouakou et al 2017). A combination of DNA barcoding with morphological analysis revealed seven ant species belonging to genera Papyrius Shattuck 1992 , Iridomyrmex Mayr 1862, Cardiocondyla nuda (Mayr 1866) group, and Camponotus novaehollandiae (Mayr 1870) group (Oberprieler et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding has been used to identify invasive ant species i.e. Solenopsis geminate (Kouakou et al 2017). This approach was used to delimit 24 morphospecies of the genus Solenopsis , which is otherwise very hard to identify to species level (Delsinne et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a continuing need for systematic review and documentation regarding the practical application of IAS management for various other invasive insects, such as the fall armyworm and locusts, which also present great threats to the local agriculture and economy. In addition, this study will have implications for newly invaded areas, such as East Asia [4,5] and West Africa [68].…”
Section: Discussionmentioning
confidence: 99%